EFEKTIVITAS MODEL DISCOVERY LEARNING PADA MATERI TEKS PROSEDUR MENGGUNAKAN MEDIA AUDIO VISUAL - Hermawan, Dimas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Learning is an interaction between teachers and students to achieve various goals, whether academic or nonacademic goals. The learning activities carried out are certainly not separate from various supporting aspects, such as teachers, students, as well as models, materials, and learning media. This study aims to measure the effectiveness of the discovery learning model on procedural text material using audio visual media. This study using a quantitative method with a quasi experimental approach, using a one group pretest-posttest design. The subjects study is the 32 students in the 2023 cohort C of Siliwangi University"™s Indonesian Language Education Study Program. The data collection technique used was testing through pre-test and post-test instruments, while the data analysis technique used was the normalized gain score (N-Gain Score) test. The study finding indicate that the discovery learning model is quite effective on procedural text material using audio visual media. The average learning outcome scores increased from 34,4 in the pre-test to 76,9 in the post-test, and resulting in an average N-Gain Score percentage of 64,9 categorized as quite effective. However in subsequent study, reevaluate the factors that might impact the learning process, including both internal and external factors that may have a indirect impact on students"™ learning results. Additionally, it is anticipated that the findings of this study would give educators or learners greater understanding in accomplishing learning goals.